Water treatment method and electrolysis device
By introducing Fe-B compounds and Ni or Co into the iron-based porous material and using high-temperature sintering method, an excellent FeB-based porous electrode material was prepared, which solved the problems of insufficient conductivity and poor stability, and significantly improved the efficiency and stability of the electrolytic device.
Patent Information
- Application Number
- CN202411639424.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing iron-based porous materials have problems such as insufficient conductivity, high cost or poor stability in electrochemical applications, which limit their application in water treatment and electrolytic devices.
FeB-based porous electrode material is prepared by introducing Fe-B compounds and using high-temperature sintering method, combining Ni or Co metals to form a multiphase composite system, which improves the conductivity, catalytic activity and structural stability of the material.
The conductivity and electrocatalytic activity of FeB-based porous electrode materials are significantly improved, mechanical strength and corrosion resistance are enhanced, and the overall electrolytic efficiency and stability of the electrolytic device are improved.
Smart Images

Figure CN119176612B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water treatment, and in particular to a water treatment method and an electrolysis device. Background Art
[0002] The invention patent with publication number CN118324262A submitted by the applicant of the present application discloses a water treatment method and an electrolysis device for treating industrial wastewater containing sodium sulfate and similar substances (such as lithium sulfate, sodium phosphate, and lithium phosphate). Taking the treatment of sodium sulfate as an example, through the electrolysis reaction of the anode and the cathode and the ability of the CEM membrane to block the passage of anions, acid sodium sulfate (NaHSO4) crystals are precipitated in the anode chamber, and hydrogen and concentrated sodium hydroxide solution are produced in the cathode chamber. As a result, not only the problem of inconvenient raw water treatment is solved, but also a variety of by-products including hydrogen can be obtained.
[0003] In an electrolysis device, the performance of the electrode materials of the anode and cathode is crucial to the overall efficiency and life of the device. Porous materials have broad application prospects in electrochemical energy storage, electrocatalysis and other fields due to their high specific surface area, abundant active sites, excellent electrochemical properties and good structural stability. The commonly used porous materials for anodes and cathodes mainly include carbon materials, precious metal materials and transition metal oxides. However, these porous materials often have problems such as insufficient conductivity, high cost or poor stability in practical applications, which limits their further development.
[0004] Iron-based materials are widely used in various electrochemical devices due to their abundant resources, low cost and environmental friendliness. However, single iron-based materials face problems such as insufficient conductivity and catalytic activity in practical applications, and need further improvement and optimization. As a new type of material, Fe-B compounds have been used in magnetic materials, cemented carbide and other fields due to their unique chemical properties and potential electrocatalytic activity. The introduction of Fe-B compounds is expected to significantly improve the comprehensive performance of iron-based materials, especially in improving their conductivity and catalytic activity. However, the application of Fe-B compounds in iron-based electrode materials, especially iron-based porous materials, has not been widely studied and reported.
[0005] Although traditional methods for preparing iron-based porous materials, such as chemical vapor deposition and electrochemical deposition, can obtain porous structures, they usually have problems such as complex processes, high costs, difficulty in large-scale production, and environmental pollution. In addition, the iron-based porous materials prepared by these methods often have disadvantages such as low mechanical strength and poor structural stability, which limit their performance in practical applications. In contrast, high-temperature sintering technology has gradually become one of the important methods for preparing porous materials due to its advantages such as simple process, easy control, low cost, and suitability for large-scale production. The preparation of iron-based porous materials by high-temperature sintering can not only significantly improve the mechanical strength and conductivity of the material, but also achieve a uniform distribution of the porous structure in the microstructure, thereby increasing the specific surface area and electrochemical activity of the material. However, the application of high-temperature sintering to the preparation of iron-based porous materials has not been reported. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a FeB-based porous electrode material with simple preparation process, excellent electrochemical performance, and significantly improved wastewater treatment efficiency, a preparation method of the FeB-based porous electrode material, a water treatment method, and an electrolysis device
[0007] In order to achieve the above object, according to the first aspect of the present invention, a FeB-based porous electrode material is provided, and the technical solution is as follows:
[0008] The FeB-based porous electrode material is obtained by high-temperature sintering of a green body including a Fe-B compound, Fe and a metal M, wherein the metal M is Ni or Co.
[0009] As a further improvement of the above-mentioned FeB-based porous electrode material: the XRD spectrum has characteristic peaks of Fe2B intermetallic compounds and Fe-M intermetallic compounds.
[0010] As a further improvement of the above-mentioned FeB-based porous electrode material: the mass ratio of Fe-B compound, Fe and metal M is (1-2.4):(1.2-1.6):1.
[0011] In order to achieve the above object, according to the second aspect of the present invention, a method for preparing a FeB-based porous electrode material is provided, and the technical scheme is as follows:
[0012] The preparation method of FeB-based porous electrode material comprises the following steps:
[0013] obtaining a mixed powder including an Fe-B compound, Fe, a metal M and a forming agent;
[0014] Pressing the mixed powder into a green body;
[0015] The green body is sintered to obtain a FeB-based porous electrode material.
[0016] As a further improvement of the above-mentioned method for preparing the FeB-based porous electrode material: the Fe-B compound is iron boride or an iron boride precursor.
[0017] As a further improvement of the preparation method of the above-mentioned FeB-based porous electrode material: the preparation method of the iron boride precursor includes the following steps: under nitrogen protection, adding a borohydride solution dropwise to a continuously stirred soluble iron salt solution, and stirring for 1 to 3 hours under ice bath conditions after the addition is completed; collecting the precipitate and washing and drying the collected precipitate to obtain the iron boride precursor.
[0018] As a further improvement to the preparation method of the above-mentioned FeB-based porous electrode material: the borohydride solution is prepared according to a ratio of adding 1 to 3 g of sodium borohydride to every 100 mL of water; the soluble iron salt solution is prepared according to a ratio of adding 5 to 6 g of ferric chloride hexahydrate to every 100 mL of water; the volume ratio of the borohydride solution to the soluble iron salt solution is 1:1.
[0019] As a further improvement of the preparation method of the above-mentioned FeB-based porous electrode material: the preparation method of the iron boride precursor includes the following steps: heating and stirring an aqueous solution containing a soluble iron salt, boric acid, citric acid, and ethylene glycol in a water bath at 70 to 90°C until a gel is formed; drying the gel in an oven at 110 to 130°C to obtain an iron boride precursor.
[0020] As a further improvement of the preparation method of the above-mentioned FeB-based porous electrode material: the aqueous solution is prepared according to the ratio of adding 7-9g ferric nitrate nonahydrate, 1-1.6g boric acid, 7-8g citric acid, and 10-30mL ethylene glycol to every 100mL water.
[0021] As a further improvement of the preparation method of the above-mentioned FeB-based porous electrode material: the sintering process is:
[0022] Raise the temperature from room temperature to 250-350°C and keep warm for 1-3 hours;
[0023] Continue to raise the temperature to 400-600°C and keep it at this temperature for 1-2 hours;
[0024] The temperature is continued to be raised to 750-850°C, kept at this temperature for 1-2 hours, and then cooled in the furnace to obtain a FeB-based porous electrode material.
[0025] In order to achieve the above object, according to the third aspect of the present invention, a water treatment method is provided, and the technical scheme is as follows:
[0026] A water treatment method comprising the steps of:
[0027] An electrolytic cell is provided, wherein the electrolytic cell has an anode liquid tank chamber and a cathode liquid tank chamber separated by a CEM membrane, and the anode of the anode liquid tank chamber and the cathode of the cathode liquid tank chamber are respectively connected to the positive and negative electrodes of a power supply;
[0028] The anolyte obtained by pre-treatment of raw water and the prepared catholyte are introduced into the anolyte tank chamber and the catholyte tank chamber respectively;
[0029] As the electrolytic cell operates, oxygen is generated in the anode liquid tank chamber and hydrogen is generated in the cathode liquid tank chamber;
[0030] The cathode adopts a FeB-based porous electrode material obtained by high-temperature sintering of a green body including a Fe-B compound, Fe and Ni; the anode adopts a FeB-based porous electrode material obtained by high-temperature sintering of a green body including a Fe-B compound, Fe and Co.
[0031] As a further improvement of the above-mentioned water treatment method: the XRD spectrum of the FeB-based porous electrode material of the cathode has characteristic peaks of Fe2B intermetallic compounds, Fe3Ni3 intermetallic compounds and Fe-Ni solid solutions; the XRD spectrum of the FeB-based porous electrode material of the anode has characteristic peaks of Fe2B intermetallic compounds and FeCo intermetallic compounds.
[0032] As a further improvement of the above water treatment method: the preparation method of FeB-based porous electrode material comprises the following steps:
[0033] obtaining a mixed powder including an Fe-B compound, Fe, Ni or Co, and a forming agent;
[0034] Pressing the mixed powder into a green body;
[0035] The green body is sintered to obtain a FeB-based porous electrode material.
[0036] As a further improvement of the above water treatment method, it also includes the steps of: placing the FeB-based porous electrode material obtained by sintering into a cavity with an electric field applied, and treating its surface in a mixed atmosphere of argon and oxygen.
[0037] As a further improvement of the above-mentioned water treatment method: taking the chamber volume as 10L as the base number, the volume of the FeB-based porous electrode material is 10-15% of the chamber volume, the pressure in the chamber is 50-100 mTorr, the RF power is 50-100W, the volume ratio of argon to oxygen in the mixed atmosphere is 4:1, the flow rate of the mixed atmosphere is 20-30sccm, and the treatment time is 5-15 minutes.
[0038] In order to achieve the above object, according to a fourth aspect of the present invention, an electrolysis device is provided, and the technical solution is as follows:
[0039] An electrolytic device, comprising an electrolytic cell, wherein the electrolytic cell has an anode liquid tank chamber and a cathode liquid tank chamber separated by a CEM membrane, wherein the anode of the anode liquid tank chamber and the cathode of the cathode liquid tank chamber are respectively connected to the positive and negative electrodes of a power supply of the electrolytic device;
[0040] The anolyte used in the anolyte tank is mainly composed of A x BO4 solution, the cathode liquid used in the cathode liquid tank chamber is AOH solution;
[0041] As the electrolytic cell operates, oxygen is generated in the anode liquid tank chamber and hydrogen is generated in the cathode liquid tank chamber;
[0042] The cathode adopts a FeB-based porous electrode material obtained by high-temperature sintering of a green body including a Fe-B compound, Fe and Ni; the anode adopts a FeB-based porous electrode material obtained by high-temperature sintering of a green body including a Fe-B compound, Fe and Co.
[0043] It can be seen that the present invention has the following advantages:
[0044] (1) The Fe-B compound introduced into the iron-based electrode material of the present invention has good electrical conductivity, which is beneficial to improving the electronic conductivity of the electrode material; excellent chemical stability, which can improve the corrosion resistance and service life of the electrode material; and potential catalytic activity, which can improve the electrochemical performance of the electrode material.
[0045] Ni exhibits good activity in electrocatalytic reactions (such as electrolysis of water), while Co has excellent performance in oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The present invention introduces Ni or Co into iron-based electrode materials, which can significantly improve the electrocatalytic activity of the electrode materials, enhance the electronic conductivity of the electrode materials, and reduce the internal resistance of the electrode materials, thereby improving the electrolysis performance of the electrolysis device for industrial wastewater.
[0046] The coexistence of Fe-B compounds, Fe and metal M (Ni or Co) forms a multiphase composite system. The components may produce a synergistic effect, provide more abundant active sites, achieve the complementarity and superposition of the advantages of each component, help regulate the overall physicochemical properties of the electrode material, and improve the electrochemical performance of the electrode material.
[0047] (2) The high-temperature sintering method is simple, easy to control, and suitable for large-scale production. It is conducive to the formation of a stable crystal structure and strong interatomic bonding, improving the mechanical strength and structural stability of the electrode material. The characteristics of the porous structure can also be controlled by regulating parameters such as sintering temperature and time.
[0048] During the high-temperature sintering process, the components in the green body will melt, diffuse and rearrange to form a microscopically uniformly distributed and interconnected porous structure; such a porous structure can provide a larger specific surface area and more active sites, which is beneficial to improving the electrochemical performance; forming a rich pore structure is beneficial to the penetration of electrolyte and the rapid transmission of ions; improving the mass transfer characteristics of the electrode material, which is beneficial to the rapid diffusion of reactants and products, thereby improving the efficiency of the electrochemical reaction; forming a dense composite structure, significantly improving the mechanical strength, corrosion resistance and structural stability of the electrode material, effectively preventing the pulverization and rupture of the electrode material during use, and extending the service life of the electrode.
[0049] (3) Compared with precious metal materials, Fe, B, Ni and Co are relatively cheap elements and are environmentally friendly; the high-temperature sintering process is relatively simple, easy to control and industrialize, with low production costs and high production efficiency. The combination of the two helps to reduce the manufacturing cost of iron-based electrode materials and reduce the impact on the environment.
[0050] (4) When applied to an electrolysis device for electrolyzing industrial wastewater, the anode is obtained by high-temperature sintering of a body including Fe-B compound, Fe and Co, while the cathode is obtained by high-temperature sintering of a body including Fe-B compound, Fe and Ni. This particular selection has the following advantages:
[0051] Anode: Anode electrolysis reactions usually involve oxidation processes (such as oxygen generation reactions). Co exhibits good electrocatalytic activity in electrochemical reactions, especially oxidation reactions, making anode reactions more efficient. Co also has excellent electrical conductivity. When combined with Fe and Fe-B compounds, it can significantly improve the conductivity of the anode and reduce the resistance of the anode, thereby improving electrolysis efficiency and reducing energy consumption.
[0052] Cathode: Cathode electrolysis reactions usually involve reduction reactions (such as hydrogen generation reactions). Ni exhibits excellent electrocatalytic activity in electrochemical reactions. The presence of Ni can significantly enhance the electrocatalytic activity of the cathode and make the cathode reaction more efficient. Ni also has good electrical conductivity. When combined with Fe and Fe-B compounds, it can significantly enhance the conductivity of the cathode, reduce the internal resistance of the cathode, and improve the electrolysis efficiency.
[0053] Therefore, the present invention significantly improves the conductivity and electrocatalytic activity of the electrode by using different metal combinations at the anode and cathode respectively, and combines the high mechanical strength and corrosion resistance brought to the porous electrode material by the high-temperature sintering method to successfully optimize the overall electrolysis efficiency and stability of the electrolysis device, so that the electrolysis device can maintain efficient and stable operation under different electrolysis conditions, and has significant technical and economic advantages.
[0054] In summary, the present invention significantly improves the conductivity, electrocatalytic activity, mechanical strength and stability of the material by introducing Fe-B compounds and Ni or Co and adopting high-temperature sintering technology, optimizes the porous structure, and improves the comprehensive performance. It has important research value and broad application prospects.
[0055] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] The drawings constituting a part of the present invention are used to assist the understanding of the present invention. The contents provided in the drawings and their related descriptions in the present invention can be used to explain the present invention, but do not constitute improper limitations on the present invention.
[0057] Figure 1 This is the XRD spectrum of FeB-Ni of Example A1 of the present invention.
[0058] Figure 2 This is a SEM photograph of FeB-Ni of Example A1 of the present invention.
[0059] Figure 3 This is a SEM photograph of FeB-Ni of Example A2 of the present invention.
[0060] Figure 4 This is the XRD spectrum of FeB-Co in Example B1 of the present invention.
[0061] Figure 5 This is a SEM photograph of FeB-Co in Example B1 of the present invention.
[0062] Figure 6 It is a schematic structural diagram of an embodiment of the electrolysis device of the present invention.
[0063] The reference numerals in the accompanying drawings are: 11-electrolytic cell, 111-CEM membrane, 112-anode, 113-cathode, 114-power supply, 115-discharge hopper, 116-solid-liquid separation device, 117-batch tank, 118-dryer, 119-pyrolysis furnace, 120-condenser. DETAILED DESCRIPTION
[0064] The present invention is described clearly and completely below in conjunction with the accompanying drawings. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the accompanying drawings, it should be particularly noted that:
[0065] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.
[0066] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0067] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.
[0068] Embodiment A1: The FeB-based porous electrode material and the preparation method thereof of this embodiment include the following steps:
[0069] A mixed powder including Fe-B compound, Fe, Ni and a forming agent is obtained, and the process is as follows: using purchased iron boride as the Fe-B compound, first putting 12g of iron boride powder, 8g of Fe powder and 5g of Ni powder into a powder mixer and mixing, then adding 1.125g of stearic acid and mixing, and after mixing, sieving with a 60-mesh sieve to obtain a mixed powder.
[0070] The mixed powder was pressed into a rectangular green body of 25×8×2 mm by a press.
[0071] The green body is sintered to obtain a FeB-based porous electrode material. The sintering process is as follows: the green body is placed in a vacuum molybdenum sheet furnace, first heated from room temperature to 300°C, and kept warm for 2 hours; then heated to 500°C, and kept warm for 2 hours; then heated to 800°C, and kept warm for 2 hours, and then cooled in the furnace to obtain a FeB-based porous electrode material, hereinafter referred to as FeB-Ni.
[0072] Figure 1 The XRD pattern of FeB-Ni in this embodiment is shown in FIG. Figure 1 As shown, FeB-Ni has characteristic peaks of Fe2B intermetallic compound, Fe3Ni3 intermetallic compound and Fe-Ni solid solution.
[0073] Figure 2 FIG. 2 is a SEM photo of FeB-Ni of this embodiment. Figure 2 As shown, FeB-Ni has a unique pore structure with abundant pores that are interconnected.
[0074] The porosity of the FeB-Ni in this embodiment was measured by the Archimedes method and found to be 35%.
[0075] The yield strength of the FeB-Ni of this embodiment is measured to be 178 MPa according to the Chinese national standard GBT 228.1-2010.
[0076] The electrochemical performance of FeB-Ni was tested using an electrochemical workstation. The working electrode of the three-electrode system was the prepared FeB-Ni, and the reference electrode was a mercury / mercury oxide electrode. The reference electrode was aligned with the center of the working electrode test surface through a Lu capillary (salt bridge) and was 1-2 mm apart. The auxiliary electrode was a platinum sheet (10 mm × 10 mm × 0.2 mm), and the test was carried out in a 1M KOH solution. Before the electrochemical test, the working electrode was sealed, and the working electrode surface exposed a working area of 0.64 square centimeters. The non-working surface was encapsulated with waterproof raw tape and 704 silicone rubber, which ensured that the current value automatically collected by the computer was the required current density. All electrochemical test data were carried out in a constant temperature water bath. Before the effective data test, the open circuit potential of the working electrode was measured using the three-electrode test method. The open circuit potential of the FeB-Ni electrode was stabilized at about -0.75V within 30 minutes. After the open circuit potential was stabilized, the electrode was tested for corresponding data.
[0077] The overpotential test process is: select the stable value of the open circuit potential as the first vertex potential, and the value of the open circuit potential dropping 2V as the second vertex potential, that is, the polarization test range is 2V, the scanning rate is 4mV / s, the electrolytic cell parameters select the reference electrode parameters corresponding to mercury / mercuric oxide, and then start the test. The test results show that the FeB-Ni in this embodiment is -10mA / cm 2 The cathode overpotential is -15mV at -100mA / cm 2 The cathode overpotential at -236mV is -10mA / cm 2 The cathode overpotential is -20 to -50 mV. The absolute value of the overpotential of the FeB-Ni in this embodiment is lower than that of the platinum electrode, and the cost is significantly reduced, so it has excellent promotion and application value.
[0078] Embodiment A2: Compared with Embodiment A1, the FeB-based porous electrode material and its preparation method of this embodiment are different in that the iron boride precursor is a Fe-B compound, and the preparation method thereof comprises the following steps: under nitrogen protection, the borohydride solution is added dropwise to the continuously stirred soluble iron salt solution, and after the addition is completed, the solution is stirred for 2 hours under ice bath conditions; the precipitate is collected and the collected precipitate is washed and dried (vacuum dried at 60°C for 12 hours) to obtain the iron boride precursor. The borohydride solution is prepared according to the ratio of adding 2g of sodium borohydride to every 100mL of water, and the soluble iron salt solution is prepared according to the ratio of adding 5.4g of ferric chloride hexahydrate to every 100mL of water, and the volume ratio of the borohydride solution to the soluble iron salt solution is 1:1.
[0079] The iron boride precursor gradually crystallizes at 400-600°C, and the required temperature range coincides with the second stage of temperature rise in the high-temperature sintering process. Therefore, using the iron boride precursor instead of directly using iron boride can not only save raw material costs and simplify the process, but also allow the crystallization of iron boride and metal alloying to proceed simultaneously, making the elements more closely combined, thereby improving the yield strength of the porous electrode material.
[0080] The XRD test showed that the FeB-Ni in this embodiment has characteristic peaks of Fe2B intermetallic compound, Fe3Ni3 intermetallic compound and Fe-Ni solid solution.
[0081] Figure 3 FIG. 2 is a SEM photo of FeB-Ni of this embodiment. Figure 3 As shown, FeB-Ni has a unique pore structure with abundant pores that are interconnected.
[0082] The porosity of the FeB-Ni in this embodiment is 37% as measured by the Archimedean method. The yield strength of the FeB-Ni in this embodiment is 185 MPa as measured according to the Chinese national standard GBT 228.1-2010.
[0083] The test results show that the cathode overpotential of the FeB-Ni in this embodiment is 12 mV at -10 mA, and the cathode overpotential at -100 mA is 232 mV.
[0084] Compared with Example A1, it can be seen that the FeB-Ni of this example not only improves the porosity and strength, but also improves the electrochemical performance to a certain extent.
[0085] Example A3: Compared with Example A2, the difference between the FeB-based porous electrode material and the preparation method of this example is that the FeB-Ni obtained by sintering is placed in a cavity with an electric field applied, and the volume of the cavity is 10L, the volume of the FeB-Ni is 10% of the volume of the cavity, the pressure in the cavity is 50mTorr, the RF power is 50W, the volume ratio of argon to oxygen in the mixed atmosphere is 4:1, the flow rate of the mixed atmosphere is 20sccm, and the processing time is 15 minutes. As a result, the high-energy argon ions formed by the ionization of argon under the action of the electric field physically collide and bombard the surface of the FeB-Ni pores, thereby significantly increasing the specific surface area of the FeB-Ni; the high-energy oxygen atoms (O) and active oxygen (O3, O2 + ), which can not only effectively remove organic pollutants, grease, oxide layers, etc., but also introduce oxygen groups on the surface of FeB-Ni pores to improve the surface hydrophilicity and chemical reactivity.
[0086] The XRD test showed that the FeB-Ni in this embodiment has characteristic peaks of Fe2B intermetallic compound, Fe3Ni3 intermetallic compound and Fe-Ni solid solution.
[0087] The porosity of the FeB-Ni in this embodiment is 39% as measured by the Archimedean method. The yield strength of the FeB-Ni in this embodiment is 181 MPa as measured according to the Chinese national standard GBT 228.1-2010.
[0088] The test results show that the cathode overpotential of the FeB-Ni in this embodiment is 11 mV at -10 mA, and the cathode overpotential at -100 mA is 218 mV.
[0089] Embodiment B1: The FeB-based porous electrode material and the preparation method thereof of this embodiment include the following steps:
[0090] A mixed powder including Fe-B compound, Fe, Co and a forming agent is obtained, and the process is as follows: using the purchased iron boride as the Fe-B compound, first putting 5g of iron boride powder, 6g of Fe powder and 5g of Co powder into a powder mixer and mixing, then adding 0.72g of stearic acid and mixing, and after mixing, sieving with a 60-mesh sieve to obtain a mixed powder.
[0091] The mixed powder was pressed into a rectangular green body of 25×8×2 mm by a press.
[0092] The green body is sintered to obtain a FeB-based porous electrode material. The sintering process is as follows: the green body is placed in a vacuum molybdenum sheet furnace, first heated from room temperature to 300°C, and kept warm for 3 hours; then heated to 500°C, and kept warm for 2 hours; then heated to 800°C, and kept warm for 1 hour, and cooled in the furnace to obtain a FeB-based porous electrode material, hereinafter referred to as FeB-Co.
[0093] Figure 4 The XRD pattern of FeB-Co in this embodiment is shown in FIG. Figure 4 As shown, FeB-Co has characteristic peaks of Fe2B intermetallic compounds and FeCo intermetallic compounds.
[0094] Figure 5 FIG. 2 is a SEM photo of FeB-Co of this embodiment. Figure 5 As shown, FeB-Co has a unique pore structure with abundant pores that are interconnected.
[0095] The porosity of the FeB-Co in this embodiment was measured by the Archimedes method and was found to be 29%.
[0096] The yield strength of FeB-Co in this embodiment is measured to be 189 MPA according to the Chinese national standard GBT 228.1-2010.
[0097] The test results show that the FeB-Co in this embodiment has a current of 10 mA / cm 2 The anode overpotential is 248mV at 100mA / cm 2 The anode overpotential at 10 mA / cm2 is 453 mV. 2 The anode overpotential is 260-290 mV. The overpotential of FeB-Co in this embodiment is lower than the overpotential of RuO2 electrode, and the cost is significantly reduced, so it has excellent promotion and application value.
[0098] Embodiment B2: Compared with Embodiment B1, the FeB-based porous electrode material and its preparation method of this embodiment are different in that the iron boride precursor is a Fe-B compound, and the preparation method comprises the following steps: heating and stirring an aqueous solution containing a soluble iron salt, boric acid, citric acid, and ethylene glycol in a 70-90°C water bath until a gel is formed; drying the gel in an oven at 110-130°C to obtain an iron boride precursor. The aqueous solution is prepared by adding 7-9g of ferric nitrate nonahydrate, 1-1.6g of boric acid, 7-8g of citric acid, and 10-30mL of ethylene glycol to every 100mL of water.
[0099] The citric acid and ethylene glycol in the iron boride precursor begin to decompose and form pores at around 250-350°C, and the FeB phase gradually crystallizes and the grains grow at 400-600°C. The required temperature range coincides with the first and second stage temperature rises of the high-temperature sintering process. Therefore, using an iron boride precursor instead of directly using iron boride can not only save raw material costs and simplify the process, but also allow the decomposition of organic matter, crystallization of iron boride and metal alloying to proceed simultaneously, allowing the elements to combine more closely, thereby improving the yield strength of the porous electrode material.
[0100] The XRD test showed that the FeB-Co in this embodiment has characteristic peaks of Fe2B intermetallic compound and FeCo intermetallic compound.
[0101] The porosity of the FeB-Co in this embodiment is 36% as measured by the Archimedean method. The yield strength of the FeB-Co in this embodiment is 191 MPA as measured according to the Chinese national standard GBT 228.1-2010.
[0102] The test results show that the anode overpotential of the FeB-Co in this embodiment is 207 mV at 10 mA and 415 mV at 100 mA.
[0103] Compared with Example B1, it can be seen that the FeB-Co in this example not only improves the porosity and strength, but also improves the electrochemical performance to a certain extent.
[0104] Example B3: Compared with Example B2, the FeB-based porous electrode material and preparation method thereof of this example are different in that the FeB-Co obtained by sintering is placed in a cavity to which an electric field is applied, and the volume of the cavity is 10L, the volume of the FeB-Co is 15% of the cavity volume, the pressure in the cavity is 100 mTorr, the RF power is 100W, the volume ratio of argon to oxygen in the mixed atmosphere is 4:1, the flow rate of the mixed atmosphere is 30sccm, and the processing time is 5 minutes.
[0105] The XRD test showed that the FeB-Co in this embodiment has characteristic peaks of Fe2B intermetallic compound and FeCo intermetallic compound.
[0106] The porosity of the FeB-Co in this embodiment is 38% as measured by the Archimedean method. The yield strength of the FeB-Co in this embodiment is 188 MPA as measured according to the Chinese national standard GBT 228.1-2010.
[0107] The test results show that the anode overpotential of the FeB-Co in this embodiment is 201 mV at 10 mA and 405 mV at -100 mA.
[0108] An embodiment of the water treatment method of the present invention comprises the following steps: setting up an electrolytic cell, wherein the electrolytic cell has an anode liquid tank chamber and a cathode liquid tank chamber separated by a CEM membrane, the anode of the anode liquid tank chamber and the cathode of the cathode liquid tank chamber being respectively connected to the positive and negative poles of a power supply; and respectively introducing the anode liquid obtained by pretreatment of raw water and the configured cathode liquid into the anode liquid tank chamber and the cathode liquid tank chamber.
[0109] Figure 6 It is a schematic structural diagram of an embodiment of the electrolysis device of the present invention.
[0110] like Figure 6 As shown, an embodiment of the electrolysis device of the present invention comprises an electrolytic cell 11, wherein the electrolytic cell 11 has an anode liquid tank chamber and a cathode liquid tank chamber separated by a CEM membrane 111, and the anode 112 of the anode liquid tank chamber and the cathode 113 of the cathode liquid tank chamber are respectively connected to the positive and negative electrodes of the power supply 114 of the electrolysis device. The cathode 113 adopts the FeB-based porous electrode material of one of the embodiments A1-A3; the anode 112 adopts the FeB-based porous electrode material of one of the embodiments B1-B3.
[0111] The anolyte used in the anolyte tank is mainly composed of A xBO4 solution, the cathode liquid used in the cathode liquid tank chamber is AOH solution. A represents a monovalent metal, B represents S element (i.e. sulfur element) or P element (i.e. phosphorus element), x=2 or 3, y=1 or 2, H represents hydrogen element, O represents oxygen element, and OH represents hydroxide ion. During the operation of the electrolytic cell 11, A is produced in the anode liquid tank chamber as the electrolytic cell 11 operates. y HBO4 crystals and oxygen, and hydrogen and AOH solution with increased concentration are produced in the cathode liquid tank chamber.
[0112] The bottom of the anode liquid tank chamber is provided with a discharge hopper 115, and the bottom of the discharge hopper 115 is provided with a discharge mechanism, which is used to discharge the A y HBO4 crystals are discharged from the anode liquid tank chamber. By providing a discharge hopper 115 at the bottom of the anode liquid tank chamber and a discharge mechanism at the bottom of the discharge hopper 115, the A generated in the anode liquid tank chamber can be discharged. y The HBO4 crystals (as NaHSO4) are conveniently discharged from the anolyte chamber.
[0113] In addition, the discharge mechanism is also connected to a solid-liquid separation device 116, which is used to separate the solid and liquid y HBO4 crystals (such as NaHSO4) are used for solid-liquid separation. The solid-liquid separation device 116 is connected to the batching tank 117 through the mother liquid reflux pipeline, and the batching tank 117 is used to prepare the anolyte. Therefore, the mother liquid separated by the solid-liquid separation device 116 will enter the batching tank 117 through the mother liquid reflux pipeline, and then return to the anolyte tank chamber for circulation.
[0114] When the A y When the HBO4 crystals are NaHSO4 crystals, the solid-liquid separation device is connected to the dryer 118, the dryer 118 is connected to the pyrolysis furnace 119, and the pyrolysis furnace 119 is respectively connected to the batching tank 117 and the condenser 120; the dryer 118 is used to dry the NaHSO4 crystals after solid-liquid separation; the pyrolysis furnace 119 is used to pyrolyze the dried NaHSO4 crystals to decompose the NaHSO4 crystals into solid Na2SO4 and gaseous H2SO4 and H2O; the condenser 120 is used to condense the gaseous H2SO4 and H2O to obtain sulfuric acid solution; the pyrolysis furnace 119 is respectively connected to the batching tank 117 and the condenser 120 through the Na2SO4 delivery pipeline and the exhaust pipeline. In this way, both the recycling of sodium sulfate and the production of sulfuric acid can be achieved.
[0115] For other process parameters of the water treatment method and other structures of the electrolysis device, please refer to the specific implementation of the invention patent with publication number CN118324262A. It has been verified that, with a saturated solution of Na2SO4 not oversaturated as the anolyte and NaOH as the cathode liquid, the hydrogen purity in the generated gas is ≥97% and the hydrogen flow rate is ≥1258mL / h when electrolyzed at a constant voltage of 3.5V for 24 hours, and the phenomenon of fragmentation and powdering will not occur after long-term use.
[0116] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.
[0117] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.
Claims
1. A water treatment method comprising the steps of: An electrolytic cell is provided, wherein the electrolytic cell has an anode liquid tank chamber and a cathode liquid tank chamber separated by a CEM membrane, and the anode of the anode liquid tank chamber and the cathode of the cathode liquid tank chamber are respectively connected to the positive and negative electrodes of a power supply; The anolyte obtained by pre-treatment of raw water and the prepared catholyte are introduced into the anolyte tank chamber and the catholyte tank chamber respectively; As the electrolytic cell operates, oxygen is generated in the anode liquid tank chamber and hydrogen is generated in the cathode liquid tank chamber; Features: The cathode adopts a FeB-based porous electrode material obtained by high-temperature sintering of a green body including a Fe-B compound, Fe and Ni; the anode adopts a FeB-based porous electrode material obtained by high-temperature sintering of a green body including a Fe-B compound, Fe and Co; The preparation method of FeB-based porous electrode material comprises the following steps: obtaining a mixed powder including an Fe-B compound, Fe, Ni or Co, and a forming agent; Pressing the mixed powder into a green body; The green body is subjected to a sintering treatment, wherein the sintering treatment comprises: Raise the temperature from room temperature to 250-350°C and keep warm for 1-3 hours; Continue to raise the temperature to 400-600°C and keep it at this temperature for 1-2 hours; Continue to raise the temperature to 750-850°C, keep it at that temperature for 1-2 hours, and cool it in the furnace to obtain the FeB-based porous electrode material.
2. The water treatment method according to claim 1, characterized in that: The XRD spectrum of the FeB-based porous electrode material of the cathode has characteristic peaks of Fe2B intermetallic compounds, Fe3Ni3 intermetallic compounds and Fe-Ni solid solutions; the XRD spectrum of the FeB-based porous electrode material of the anode has characteristic peaks of Fe2B intermetallic compounds and FeCo intermetallic compounds.
3. The water treatment method according to claim 1, characterized in that: The method also includes the steps of: placing the FeB-based porous electrode material obtained by sintering into a cavity with an electric field applied, and treating its surface in a mixed atmosphere of argon and oxygen.
4. The water treatment method according to claim 3, characterized in that: Taking the chamber volume as 10L as the base number, the volume of the FeB-based porous electrode material is 10-15% of the chamber volume, the pressure in the chamber is 50-100 mTorr, the RF power is 50-100W, the volume ratio of argon to oxygen in the mixed atmosphere is 4:1, the flow rate of the mixed atmosphere is 20-30sccm, and the processing time is 5-15 minutes.
5. The water treatment method according to claim 1, characterized in that: The Fe—B compound is iron boride or an iron boride precursor.
6. The water treatment method according to claim 5, characterized in that: The preparation method of the iron boride precursor comprises the following steps: under nitrogen protection, dropping a borohydride solution into a continuously stirred soluble iron salt solution, stirring for 1 to 3 hours in an ice bath after the dropping is completed; collecting a precipitate and washing and drying the collected precipitate to obtain the iron boride precursor.
7. The water treatment method according to claim 5, characterized in that: The preparation method of the iron boride precursor comprises the following steps: heating and stirring an aqueous solution containing a soluble iron salt, boric acid, citric acid and ethylene glycol in a water bath at 70-90° C. until a gel is formed; and drying the gel in an oven at 110-130° C. to obtain the iron boride precursor.
8. An electrolysis device, comprising an electrolysis cell, wherein the electrolysis cell has an anode liquid tank chamber and a cathode liquid tank chamber separated by a CEM membrane, wherein the anode of the anode liquid tank chamber and the cathode of the cathode liquid tank chamber are respectively connected to the positive and negative electrodes of the power supply of the electrolysis device; As the electrolytic cell operates, oxygen is generated in the anode liquid tank chamber and hydrogen is generated in the cathode liquid tank chamber; Features: The cathode adopts a FeB-based porous electrode material obtained by high-temperature sintering of a green body including a Fe-B compound, Fe and Ni; the anode adopts a FeB-based porous electrode material obtained by high-temperature sintering of a green body including a Fe-B compound, Fe and Co; The preparation method of FeB-based porous electrode material comprises the following steps: obtaining a mixed powder including an Fe-B compound, Fe, Ni or Co, and a forming agent; Pressing the mixed powder into a green body; The green body is subjected to a sintering treatment, wherein the sintering treatment comprises: Raise the temperature from room temperature to 250-350°C and keep warm for 1-3 hours; Continue to raise the temperature to 400-600°C and keep it at this temperature for 1-2 hours; Continue to raise the temperature to 750-850°C, keep it at that temperature for 1-2 hours, and cool it in the furnace to obtain the FeB-based porous electrode material.
Citation Information
Patent Citations
Water treatment method and electrolysis device
CN118324262A
Porous nickel-based cathode material for hydrogen evolution reaction and preparation method thereof
CN107190279A
Amorphous alloy mesh, preparation method thereof and application of amorphous alloy mesh in sewage treatment
CN111020411A